Interview with Mozaffar Ahmed, president of NAP (National Awami Party), former communist leader, advisor of Mujib Nagar Govt in 1971. Interviewed by Kabir - Kabir, Shahriar.
Interview with Mozaffar Ahmed, president of NAP (National Awami Party), former communist leader, advisor of Mujib Nagar Govt in 1971. Interviewed by Kabir.